Max Weber and Charles Peirce : at the crossroads of science, philosophy, and culture - Koshul, Basit Bilal, 1968- (Lexington Books, 2014)
Max Weber and Charles Peirce: At the Crossroads of Science, Philosophy, and Culture marks the first time that the leading European social scientist, Max Weber has been brought into conversation with the leading American philosopher, Charles Peirce. This conversation helps us to not only better understand the challenges that are facing global modernity at the beginning of the 21st century but also points to creative ways to redress them.